Phage vB_KlebPS_265 Active Against Resistant/MDR and Hypermucoid K2 Strains of Klebsiella pneumoniae - Vyacheslav I. Yakubovskij; Vera V. Morozova; Yuliya N. Kozlova; Artem Yu. Tikunov; Valeria A. Fedorets; Elena V. Zhirakovskaya; Igor V. Babkin; Alevtina V. Bardasheva; Nina V. Tikunova (Viruses)
Klebsiella pneumoniae is an important opportunistic pathogen often resistant to antibiotics. Specific phages can be useful in eliminating infection caused by K. pneumoniae. Klebsiella phage vB_KlebPS_265 (KlebP_265) and its host strain were isolated from the sputum of a patient with Klebsiella infection. KlebP_265 was specific mainly to K. pneumoniae-type K2 strains including hypermucoid strains. Most of the hypermucoid KlebP_265-susceptible strains were antibiotic-resistant. This siphophage demonstrated good lytic activity and stability. The KlebP_265 genome was 46,962 bp and contained 88 putative genes; functions were predicted for 37 of them. No genes encoding integrases, toxins, or antibiotic resistance were found in the genome. So, KlebP_265 could potentially be a therapeutic phage. Comparative analysis indicated that KlebP_265 with the most relative Klebsiella phage DP01 formed the putative Dipiunovirus genus. Genome analysis revealed a large monophyletic group of phages related to KlebP_265 and DP01. This group is divided into two monophyletic clusters of phages forming new putative subfamilies Skatevirinae and Roufvirinae. Phylogenetic analysis showed extensive gene exchange between phages from the putative subfamilies. Horizontal transfer even involved conservative genes and led to clear genomic mosaicism, indicating multiple recombination events in the ancestral phages during evolution.